Optimal control over the heat field in thin bodies local constraints on control - Kapustyan, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
Asymptotic solutions of problems of optimal locally constrained control over the heat field in thin bodies are constructed and justified. These problems relate to the critical case of singularly perturbed systems (the degenerate problem has a family of solutions).